Pemanfaatan Teknologi Informasi untuk Meningkatkan Kemampuan Penyusunan Laporan Keuangan Berbasis Digital bagi Guru MGMP Akuntansi SMK di Kabupaten Kulon Progo: Utilization of Information Technology to Improve the Ability to Prepare Digital-Based Financial Statements for Vocational Accounting MGMP Teachers in Kulon Progo Regency - Wibawa, Eka Ary; Hakim, Arif Rahman; Siswanto, Siswanto; Yudhiyati, Ratna (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Along with the development of the increasingly massive digital era, technological skills have become very important for every profession, including accounting teachers. Accounting teachers need to have the ability to compile digital-based financial statements because they are at the forefront of preparing accounting graduates who will compete in the professional and modern world of work. Analysis of the situation shows that the teacher of MGMP Accounting SMK Kulon Progo. The participants of the PkM activity were 21 teachers of MGMP Accounting for SMK Kulon Progo Regency. The steps of PKM activities are 1) the urgency of the ability to prepare digital-based financial statements for teachers 2) the practice of preparing journals and ledgers with Microsoft Excel, 3) the practice of preparing adjustment journals and financial statements with Microsoft Excel, 4) direction and technical explanation for the assignment of independent worksheet work, 5) independent work by teachers for 2 weeks, 6) presentation of independent work, and 7) dedication to reviewing the practical task of preparing digital-based financial statements. The result of PKM activities is the increasing ability of accounting teachers to compile digital-based financial statements. The achievement of PkM results is supported by several factors, namely the solidity of the service team, cooperation agreements between the service team and partners, smooth communication between the service team and partners, and the suitability of training materials with the needs of target partners.